2016
DOI: 10.5935/0004-2749.20160016
|View full text |Cite
|
Sign up to set email alerts
|

Early post-LASIK flap amputation in the treatment of aggressive, branching keratitis: a case report

Abstract: Infectious keratitis is rare following laser vision correction. We present a case of aggressive fungal keratitis caused by Aspergillus flavus, following laser in situ ke ratomileusis (LASIK) in the setting of a unique environmental risk factor. We describe the key features of the acute case presentation, which guided empirical medical and surgical treatment, resulting in the most favorable outcome found in the literature, to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…1 These complications are often challenging to treat, and flap amputation is sometimes necessary to adequately control corneal disease. Infectious keratitis 2–4 and epithelial ingrowth 5–9 have previously been reported as the most common indications for flap amputation, and our findings were in agreement. In our series, although flap amputation assisted in controlling the underlying disease process in all cases with overall satisfactory final vision, some eyes required significant further intervention or sustained loss of best visual acuity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1 These complications are often challenging to treat, and flap amputation is sometimes necessary to adequately control corneal disease. Infectious keratitis 2–4 and epithelial ingrowth 5–9 have previously been reported as the most common indications for flap amputation, and our findings were in agreement. In our series, although flap amputation assisted in controlling the underlying disease process in all cases with overall satisfactory final vision, some eyes required significant further intervention or sustained loss of best visual acuity.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the final median best visual acuity was 20/25, similar to that reported by other investigators. 2–4,7–9 Chhadva et al 3 found better UCVA after flap amputation for epithelial ingrowth (20/30, 3 eyes) than for infectious keratitis (20/50, 5 eyes). Our findings were similar with better final median best visual acuity in noninfectious cases compared with infectious cases after correcting for significant irregular astigmatism from corneal scarring by using rigid contact lenses.…”
Section: Discussionmentioning
confidence: 99%